2012
DOI: 10.1016/j.neurobiolaging.2010.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo cultures of microglia from young and aged rodent brain reveal age-related changes in microglial function

Abstract: To understand how microglial cell function may change with aging, various protocols have been developed to isolate microglia from the young and aged central nervous system (CNS). Here we report modification of an existing protocol that is marked by less debris contamination and improved yields and demonstrates that microglial functions are varied and dependent on age. Specifically, we found that microglia from aged mice constitutively secrete greater amounts of interleukin-6 (IL-6) and tumor necrosis factor-α … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
244
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(260 citation statements)
references
References 64 publications
10
244
0
6
Order By: Relevance
“…Through depletion of microglia from runner hippocampi or their addition to neurosphere preparations from sedentary mice, we have been able to provide the first direct evidence that the positive effect of voluntary exercise on NPC activity within the hippocampus is dependent on microglia. In line with the prevailing scientific view that microglia are more proinflammatory in the aging brain, and to some degree dysfunctional (Conde and Streit, 2006;Njie et al, 2012), we were able to demonstrate that removal of microglia from preparations of 9-and 20-month-old mice increased the neurosphere formation frequency. Thus, hippocampal microglia directly and differentially influence NPC activity in situ in two physiological paradigms: exercise and aging.…”
Section: Role Of Microglia In Neural Precursor Activationsupporting
confidence: 88%
See 1 more Smart Citation
“…Through depletion of microglia from runner hippocampi or their addition to neurosphere preparations from sedentary mice, we have been able to provide the first direct evidence that the positive effect of voluntary exercise on NPC activity within the hippocampus is dependent on microglia. In line with the prevailing scientific view that microglia are more proinflammatory in the aging brain, and to some degree dysfunctional (Conde and Streit, 2006;Njie et al, 2012), we were able to demonstrate that removal of microglia from preparations of 9-and 20-month-old mice increased the neurosphere formation frequency. Thus, hippocampal microglia directly and differentially influence NPC activity in situ in two physiological paradigms: exercise and aging.…”
Section: Role Of Microglia In Neural Precursor Activationsupporting
confidence: 88%
“…However, most of these investigations used neocortical microglia preparations derived from newborn pups and maintained in culture for extended periods of time. As microglial phenotypes appear to differ across brain regions and ages (Lawson et al, 1990;Ren et al, 1999;Kim et al, 2000;Butovsky et al, 2006;Njie et al, 2012), any conclusions drawn from these studies would be difficult to extrapolate to adult hippocampal neurogenesis.…”
Section: Role Of Microglia In Neural Precursor Activationmentioning
confidence: 99%
“…Aged microglia have an increased proinflammatory response and shift toward the M1 phenotype. Basal and stimulated secretion of TNF-α and IL-6 were increased in the ex vivo culture of senescent microglia [203], and hypertrophic morphological changes in the aged cells were observed [197,204,205]. Consistent with this evidence, an in vivo study showed that iNOS, TNF-α, and IL-6 were elevated, while arginase-1 was repressed in the midbrain of aged mice [206].…”
Section: Agingsupporting
confidence: 56%
“…In demyelinating models, reduced migration of mononuclear cells [198], and impaired clearance of myelin debris in macrophages accompanied by an age-associated delay in remyelination have been observed [199][200][201]. Additionally, microglia isolated from aged mice displayed a reduced capability to engulf Aβ compared with young mice [202,203]. Studies have shown that aging differentially affects the inflammatory response between microglia and peripheral macrophages.…”
Section: Agingmentioning
confidence: 99%
“…Similar dystrophic microglia have been reported in rodent mouse models of accelerated aging and neurodegeneration (Hasegawa‐Ishii et al ., 2011). Microglia from aged mice and Alzheimer's mouse models were shown to phagocytose and degrade less amyloid beta peptide (Aβ), thereby contributing to the disease process (Hickman et al ., 2008; Njie et al ., 2012). As dystrophy in microglia is restricted to aged and neurodegenerative brain tissues, it has been proposed to be the consequence of age‐associated telomere shortening and replicative senescence in microglia (Flanary et al ., 2007).…”
Section: Introductionmentioning
confidence: 99%